2015
DOI: 10.1111/1744-7941.12075
|View full text |Cite
|
Sign up to set email alerts
|

Working longer: What is the relationship between person-environment fit and retirement intentions?

Abstract: This paper examines the role of person-environment (P-E) fit in encouraging longer working lives in a sample of Australian public servants. Study results are of interest to those involved in the development of effective HRM policy aimed at retention of older workers. A sample of 332 workers aged 40 and over, completed a questionnaire. Multivariate regression analyses were used to identify the most important predictors of intention to retire. Focus group interviews (n = 42) were also undertaken. Age and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 68 publications
3
26
1
1
Order By: Relevance
“…Howe et al. ; Oakman and Wells ; Skinner et al. ), and King, Wei and Howe () concluded that turnover in aged care should be addressed by focusing on policy and management issues, such as satisfaction with work schedules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howe et al. ; Oakman and Wells ; Skinner et al. ), and King, Wei and Howe () concluded that turnover in aged care should be addressed by focusing on policy and management issues, such as satisfaction with work schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been undertaken exploring different facets of the P–E fit model, for example, person–organisation (P–O), person–job (P–J), person–supervisor (P–S), and person–group (P–G) fit, and the impact of different types of fit on outcomes such as turnover intentions (Ahmad ; Cable and DeRue ), job satisfaction (Cable and DeRue ; Hardin and Donaldson ), mental health and subjective well‐being (Chu ; Park et al. ), and retirement intentions (Oakman and Wells ). This model has also been used in the occupational stress literature and by ergonomists working in occupational health and safety (Bakker and Demerouti ; Macdonald ) to explore the relationship between demands required to complete work tasks, resources available to individuals, and the impact on individual outcomes resulting from the degree of fit between demands and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Through age-conscious HR policies, employers can offer work accommodations that maintain the functions of older workers (Fabisiak & Prokurat 2012;Fuertes et al 2013;Ilmarinen 2006), corresponding to potential motivational changes over the life course (Carstensen 1995;Kanfer & Ackerman 2004). To be successful, age-management initiatives must be adapted to the complex decision-making process that employees use before retirement, recognizing the importance of individual differences (Fridriksson et al 2017;Nilsson 2016;Nilsson et al 2011;Oakman & Wells 2016) and that top-management support can be critical for successfully managing diversity-including of age-at the workplace level (Kossek et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Shultz (2010) highlighted a need for new theoretical directions to improve understanding of factors influencing retirement decisions. For example, Oakman and Wells (2015) found that good PE fit can contribute to an extended working life. For example, Oakman and Wells (2015) found that good PE fit can contribute to an extended working life.…”
Section: Introductionmentioning
confidence: 99%
“…One potentially useful direction is incorporating a person-environment (PE) fit framework into decisions related to retirement. For example, Oakman and Wells (2015) found that good PE fit can contribute to an extended working life.…”
Section: Introductionmentioning
confidence: 99%